Finite element investigations on the microstructure of composite materials - Maligno, Angelo Rosario (2008)
This thesis describes the investigation and development of damage modelling for composites materials at their micro-scale (e.g. fibre, matrix). A damage model for elastic materials, based on a "local" damage approach, has been introduced to predict failure onset and simulate the post-failure behaviour of unidirectional threedimensional representative volume elements (RVE) or unit cells with hexagonal distribution of the fibres over the cross section. The damage model consists of three parts: an elastic model, a failure criterion and the post-failure behaviour. Modifications of von Mises criteria and Maximum Principal Stress criterion have been considered to evaluate failure in the matrix whilst for the fibre in general the Maximum Principal Stress criterion has been used. The damage model has been implemented into the commercial code ABAQUS with subroutines in FORTRAN (UMAT and USDFLD).